PEMBERDAYAAN MASYARAKAT MELALUI PEMANFAATAN LAHAN TIDUR MENJADI TEMPAT WISATA BANTO ROYO DI JORONG KALUANG TAPI NAGARI KOTO TANGGAH KECAMATAN TILATANG KAMANG KABUPATEN AGAM - Sari Dusni (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2021)
This study aims to determine the stages of community empowerment through the use of idle land to become tourist attractions in Jorong Kaluang Tapi Nagari Koto Tanggah, Tilatang Kamang District, Agam Regency and its impact on the community. The method used is a qualitative method with descriptive research that describes the conditions that occur in the field related to community development through the use of idle land to become tourist attractions. Sources of research are staff who manage the Banto Royo tourist attraction and the community as well as other supporting data. Data collection was carried out by means of observation, interview and documentation techniques. The results of the study revealed that the stages of community empowerment through the use of idle land to become a place for Banto Royo Tourism in Jorong Kaluang Tapi Nagari Koto Tanggah, Tilatang Kamang District, Agam Regency, namely the awareness stage, the approach stage, the action plan formalization stage, implementation, participation and evaluation. The impact on society is economic empowerment, religion, building construction, education and employment.